Enhanced Thermal Oxidation Stability of Reduced Graphene Oxide by Nitrogen Doping. Issue 38 (12th August 2014) - Sandoval, Stefania; Kumar, Nitesh; Sundaresan, A.; Rao, C. N. R.; Fuertes, Amparo; Tobias, Gerard
Abstract Nitrogen‐doped reduced graphene oxide (N‐doped RGO) samples with a high level of doping, up to 13 wt. %, have been prepared by annealing graphene oxide under a flow of pure ammonia. The presence of nitrogen within the structure of RGO induces a remarkable increase in the thermal stability against oxidation by air. The thermal stability is closely related with the temperature of synthesis and the nitrogen content. The combustion reaction of nitrogen in different coordination environments (pyridinic, pyrrolic, and graphitic) is analyzed against a graphene fragment (undoped) from a thermodynamic point of view. In agreement with the experimental observations, the combustion of undoped graphene turns out to be more spontaneous than when nitrogen atoms are present.